The global burden of metabolic disease: Data from 2000 to 2019 - Chew, Nicholas W S; Ng, Cheng Han; Tan, Darren Jun Hao; Kong, Gwyneth; Lin, Chaoxing; Chin, Yip Han; Lim, Wen Hui; Huang, Daniel Q; Quek, Jingxuan; Fu, Clarissa Elysia; Xiao, Jieling; Syn, Nicholas; et al. (Cell metabolism, 2023)
Global estimates of prevalence, deaths, and disability-adjusted life years (DALYs) from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019 were examined for metabolic diseases (type 2 diabetes mellitus [T2DM], hypertension, and non-alcoholic fatty liver disease [NAFLD]). For metabolic risk factors (hyperlipidemia and obesity), estimates were limited to mortality and DALYs. From 2000 to 2019, prevalence rates increased for all metabolic diseases, with the greatest increase in high socio-demographic index (SDI) countries. Mortality rates decreased over time in hyperlipidemia, hypertension, and NAFLD, but not in T2DM and obesity. The highest mortality was found in the World Health Organization Eastern Mediterranean region, and low to low-middle SDI countries. The global prevalence of metabolic diseases has risen over the past two decades regardless of SDI. Urgent attention is needed to address the unchanging mortality rates attributed to metabolic disease and the entrenched sex-regional-socioeconomic disparities in mortality.